Development of new regimens for tuberculosis - Ma, Zhenkun (Henry Stewart Talks, 2013)
Current therapies against tuberculosis and unmet needs, Desired profile for new TB drug regimen, Current approaches in TB drug development, New approaches in TB regimen development